Thermal structure and evolution of an Archean large hot orogen : Insights from the Tasiusarsuaq terrane, SW Greenland - Dziggel, A.; Diener, J. F.A.; Kokfelt, T. F.; Kolb, J.; Scherstén, A. (Precambrian Research, 2019)
The Tasiusarsuaq terrane represents an Archean continental upper plate that was assembled and thickened by a series of igneous and tectonic events between c. 2970 and 2700 Ma. A review of the available data combined with thermodynamic modelling and U-Pb titanite and zircon dating allows detailed insight into the processes of crustal growth during the Meso- and Neoarchean. Following the intrusion of the c. 2970–2950 Ma Fiskenæsset complex in an arc-type setting, the southern part of the Tasiusarsuaq terrane was intruded by an early TTG generation between c. 2920 and 2880 Ma to create the Bjørnesund block. Subsequently, from c. 2880 to 2830 Ma, TTG magmatism migrated to the Sermilik block in the central and northern part of the Tasiusarsuaq terrane, whereas monzogranite magmatism occurred in the south. We interpret this pattern of igneous activity to be a result of accretion of the Sermilik block to the Bjørnesund block and the formation of a new plate interface behind the accreted terrane. Fabrics related to this early accretionary stage are preserved in the prograde amphibolite facies (580–630 °C; 4–6 kbar) lithologies from the Bjørnesund block that have U-Pb titanite ages of c. 2820 Ma. Afterwards, ongoing southwards-directed subduction led to substantial thickening, manifested by high-pressure granulite facies metamorphism (870 °C, 9.0–9.2 kbar) and the intrusion of the c. 2805–2785 Ma Ilivertalik intrusive complex. Convergence and underthrusting by Eoarchean continental crust (Færingehavn terrane) at c. 2760 to 2720 Ma led to the extrusion of hot, ductile granulite nappes into the mid crust. At this time, large sections of the Tasiusarsuaq terrane underwent extensive amphibolite facies reworking, at conditions ranging from ~725 °C to 5.0–5.5 kbar in the central parts to 6.5–7 kbar and 700 °C in the north. These conditions lasted until the final collision of the terranes at 2720–2700 Ma. Collectively, our model describes the evolution of an Archean large hot orogen that is characterized by continuous ...